2007
DOI: 10.1089/neu.2007.0339
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging Improves Outcome Prediction in Adult Traumatic Brain Injury

Abstract: In patients with traumatic brain injury (TBI), diffuse axonal injury (DAI) accounts for a significant amount of parenchymal injury. Diffusion weighted magnetic resonance imaging (DWI) is known to be sensitive for detecting visible DAI lesions. We focused on detection of non-visible, quantifiable diffusion changes in specific normal-appearing brain regions, using apparent diffusion coefficient (ADC) maps. Thirty-seven adults with TBI were compared to 35 age-matched control patients. DWI was performed and ADC ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 40 publications
0
34
2
2
Order By: Relevance
“…Our findings are contradictory to those of some other smaller studies of normal-appearing white matter, 11,13 and could be explained by the differing examination time points of the early MRI or the different regions studied. However, both at 3 and 12 months post-injury, we demonstrated a higher mean ADC value in region IV than in the control group.…”
Section: Mean Adc Values and Comparison With Controlscontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are contradictory to those of some other smaller studies of normal-appearing white matter, 11,13 and could be explained by the differing examination time points of the early MRI or the different regions studied. However, both at 3 and 12 months post-injury, we demonstrated a higher mean ADC value in region IV than in the control group.…”
Section: Mean Adc Values and Comparison With Controlscontrasting
confidence: 99%
“…[11][12][13] A DWI study of chronic TBI patients demonstrated increased mean ADC values in both visible lesions and normal-appearing tissue in the corpus callosum. 14 This finding corresponds to the increased MD observed in later DTI studies 5,15,16 and such changes in indices of diffusion are considered to reflect pathology in microstructure and architectural organization.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have described the utility of conventional MRI sequences, [18][19][20] diffusion-weighted imaging, 21,22 DTI, 23,24 and susceptibility-weighted imaging 25,26 in patients with TBI. This literature demonstrates the superiority of MRI over CT for the visualization of lesions.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…33 Previous studies suggest that changes of ADC values in the corpus callosum and BS are associated with the outcomes. 23,34,35 We quantitatively tested the water diffusion in the predilection areas of DAI (CS, corpus callosum and BS) and found that the increased ADC values in patients with TBI were comparable to those in the control subjects, which can be explained by the compromised obstruction of the broken axonal membrane, or they may be due to residual oedema. The ADC values in the CCS and BS were significantly increased in patients with unfavourable outcomes, and the ADC ccs proved to be an independent risk factor for poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ADC map was automatically generated by the work station, and 12 regions of interest (ROIs) were manually drawn in the predilection areas of DAI, 23 and their ADC values were recorded ( Figure 1). The ROIs included the following structures: bilateral centrum semiovale (CS), genu, body and splenium of the corpus callosum (CCS) and BS.…”
Section: Mri Analysismentioning
confidence: 99%